Transposon Tn916 mutagenesis in Bacillus anthracis. - Ivins, B E (1988)
Mutagenesis of Bacillus anthracis by the streptococcal tetracycline resistance transposon Tn916 is described. Tn916 was transferred from Streptococcus faecalis DS16C1 to B. anthracis VNR-1 by conjugation in a standard filter mating procedure. Tetracycline-resistant (Tcr) transconjugants were obtained at a frequency of 1.6 X 10(-8) per donor CFU. When donor and recipient cells were treated with nafcillin before conjugation, the frequency was increased nearly 10-fold. Nafcillin pretreatment of donor and recipient strains was used in all subsequent conjugation experiments. S.faecalis CG110, containing multiple chromosomal insertions of Tn916, transferred the transposon to B. anthracis VNR-1 at a frequency of 9.3 x 10(-5). A Tcr B. anthracis transconjugant, strain VNR-1-tet-1, transferred Tn916 to B. anthracis UM23-1 and Bacillus subtilis BST1 at frequencies of 2.1 x 10(-4) and 5.8 X 10(-6), respectively. The transfer of Tn916 occurred only on membrane filters, since no Tcr transconjugants were obtained when strains VNR-1-tet-1 and UM23-1 were mixed and incubated in broth culture. The presence of the Tn916-associated tetM gene in Tcr B. anthracis and B. subtilis transconjugants was confirmed in hybridization experiments by using a 5-kilobase-pair DNA fragment containing the tetM gene as a probe. Of 3,000 B. anthracis UM23-1 Tcr transconjugants tested, 21 were phenylalanine auxotrophs and 2 were auxotrophic for phenylalanine, tyrosine, and tryptophan.